THE PRESERVATION SOME INDIAN FRESH WATER FISH - DURAIRAJ, S; KRISHNAMURTHI, S (Fishery Technology, 2017)
Quality changes in Labeo rohita; Cirrhinus mrigala and Tilapia mossambica were studied during storage in ice and at ambient temperature (29-32Â°C). After 10 h at ambient temperature L. rohita and T. mossambica were completely spoiled, while C. mrigala became unacceptable within 11 h.